2008
DOI: 10.3201/eid1405.071301
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic Influenza Planning in the United States from a Health Disparities Perspective

Abstract: We explored how different socioeconomic and racial/ ethnic groups in the United States might fare in an infl uenza pandemic on the basis of social factors that shape exposure, vulnerability to infl uenza virus, and timeliness and adequacy of treatment. We discuss policies that might differentially affect social groups' risk for illness or death. Our purpose is not to establish the precise magnitude of disparities likely to occur; rather, it is to call attention to avoidable disparities that can be expected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
234
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(238 citation statements)
references
References 24 publications
(19 reference statements)
2
234
0
2
Order By: Relevance
“…Several studies have shown that risk communication for communicable diseases has failed to reach intended communities particularly those most at risk (Blumenshine et al, 2008;Braverman, Egerter, Cubbin, & Marchi, 2004;Crouse Quinn, 2008;Reynolds, 2007). To understand why, there is a need for research that captures the breadth, depth, and variability of public comprehensions and perceptions of risk; optimal sources of risk information; and common health beliefs, especially among minority and hardto-reach communities (Blanchard et al, 2005;Elledge, Brand, Regens, & Boatright, 2008;Morrison & Yardley, 2009;Voeten et al, 2009).…”
Section: Evidence Gapsmentioning
confidence: 97%
“…Several studies have shown that risk communication for communicable diseases has failed to reach intended communities particularly those most at risk (Blumenshine et al, 2008;Braverman, Egerter, Cubbin, & Marchi, 2004;Crouse Quinn, 2008;Reynolds, 2007). To understand why, there is a need for research that captures the breadth, depth, and variability of public comprehensions and perceptions of risk; optimal sources of risk information; and common health beliefs, especially among minority and hardto-reach communities (Blanchard et al, 2005;Elledge, Brand, Regens, & Boatright, 2008;Morrison & Yardley, 2009;Voeten et al, 2009).…”
Section: Evidence Gapsmentioning
confidence: 97%
“…Most messages focused on protection from smoke inhalation among those in affected areas. An important part of any messaging is the development and timely release of effective health risk communication to encourage behaviors to limit negative health impacts (Vaughan & Tinker, 2009), especially among vulnerable populations (Blumenshine et al, 2008;Vlahov, Coady, Ompad, & Galea, 2007). Few previous studies have looked at effective risk communication during wildfires or analyzed the effect of technical message content, especially among vulnerable groups.…”
mentioning
confidence: 98%
“…Furthermore, Blumenshine et al (7) suggested that various factors determine the severity of pandemic influenza, including differential exposure to influenza due to income or ethnicity, unequal levels of susceptibility, differential access to prophylaxis, and treatment after disease develops. A study in the United States reported higher rate of hospitalization among Asian/Pacific Islanders, non-Hispanic blacks, and Hispanics compared with non-Hispanic whites during the 2009 pandemic (30).…”
Section: Discussionmentioning
confidence: 99%